Antinociceptive activity of methanolic extract of Acmella uliginosa (Sw.) Cass. - Ong, Hui Ming; Tengku Mohamad, Tengku Azam Shah; Makhtar, Nor ‘Adilah; Khalid, Mohamed Hanief; Khalid, Syamimi; Perimal, Enoch Kumar; Mastuki, Siti Nurulhuda; Zakaria, Zainul Amiruddin; Lajis, Nordin; Israf Ali, Daud Ahmad; Sulaiman, Mohd Roslan (Elsevier, 2011)
Ethnopharmacological relevance: Acmella uliginosa (Sw.) Cass. is a medicinal herbaceous plant that is commonly used by the Malay community in Malaysia to relieve pain often associated with mouth ulcers, toothache, sore throat, and stomach ache. Aim: The study was carried out to investigate the antinociceptive effect of the methanolic extract of A. uliginosa (Sw.) Cass. flowers (MEAU) using murine models of chemicals and thermal nociception. Materials and methods: Chemicals (acetic acid-induced abdominal constriction and formalin-, capsaicin-, glutamate-induced paw licking test) and thermal models (hot plate test) of nociception in mice were employed to evaluate the MEAU analgesic effect. The extract was given via oral administration at doses of 3, 10, 30 and 100 mg/kg. Results: It was demonstrated that MEAU produced significant antinociceptive response in all the chemical- and thermal-induced nociception models, which indicates the presence of both centrally and peripherally mediated activities. Furthermore, the reversal of antinociception of MEAU by naloxone suggests the involvement of opioid system in its centrally mediated analgesic activity. Moreover, MEAU-treated mice did not show any significant motor performance alterations. No mortality and signs of toxicity were recorded following treatment of the MEAU. Conclusion: The results from the present study appear to support the folkloric belief in the medicinal properties of A. uliginosa (Sw.) Cass. which against pain at both central and peripheral levels, in which the central antinociception is probably due to the participation of the opioid receptors.